2022
DOI: 10.1186/s12912-022-01132-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of procrastination in providing nursing care among Iranian nursing staff

Abstract: Aim This study aimed to investigate procrastination in nursing care providing. Design This descriptive cross-sectional study was carried out on 125 nurses in ICUs, PICUs, NICUs, and surgery wards, who were selected by census sampling in Iran. Methods The data were collected using the Procrastination Scale, which consisted of 25 items relating to 3 factors. Data were analyzed using statistics, Chi-squar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Management interventions play a key role in improving patient safety (32,36) and should be given more attention in order to achieve effective communication and the efficient teamwork and obtain positive feedback. Protecting manpower is the most important action that results in increased job satisfaction, organizational belonging, and better performance among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Management interventions play a key role in improving patient safety (32,36) and should be given more attention in order to achieve effective communication and the efficient teamwork and obtain positive feedback. Protecting manpower is the most important action that results in increased job satisfaction, organizational belonging, and better performance among caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Abd Allah and Mohamed (2018) also indicated that the mean children's behavioral pain scoring in no distraction group was higher than both active and passive distraction groups and there was a statistically significant difference between mean of children's behavioral pain scoring in the three groups [19] . Beside, Kaheni and Rezai (2016) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] reached to the same result who illustrated that mean children's behavioral pain response scoring was higher in no distraction group than active distraction group there was a significant difference in the score of behavioral responses to pain between the two groups [20] . The pain intensity was significantly lowered in the study group and that is typically supported in the work of Elsayed, Bahgat and El-Afifi (2018) [11] when they studied on 75 hospitalized school age children to determine the effect of active versus passive distraction technique on controlling pain associated with invasive nursing procedures and found that there was statistically significant difference between pain intensity in active and passive distraction groups and between control groups.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of researches were done to explore its negative impact on children health and only few started to explore the possible good uses of it in relation to child growth and development. However; playing with an interactive game is considered an active method of pain distraction [14] . Even though the field of virtual reality/video games, computer games, mobile or tablet games are the hope of future nonpharmacological active distraction pain management worldwide among pediatric as well as adult patients, still this technique in under-explored and even underused by the Egyptian pediatric nurses in a way that is helpful in pain reduction.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluasi kinerja adalah suatu proses yang digunakan oleh pimpinan untuk menentukan prestasi kerja seorang karyawan dalam melaksanakan tugasnya sesuai dengan tanggung jawab dan standar kinerja yang telah ditetapkan sebelumnya (Amjad et al, 2021). (Schut et al, 2021) (Babaie et al, 2022) Evaluasi kinerja merupakan proses penilai pejabat yang melakukan penilaian (appraisal) mengumpulkan informasi mengenai kinerja ternilai-pegawai yang dinilai (appraisal) yang didokumentasikan secara formal untuk menilai kinerja ternilai dengan membandingkannya dengan standar kinerja secara periodik untuk membantu pengambilan keputusan manajemen sumber daya manusia.…”
Section: Pendahuluanunclassified